Microplate Agglutination Test for Canine Brucellosis Using Recombinant Antigen-Coated Beads. (28th October 2014) - Castillo, Yussaira; Tachibana, Masato; Kimura, Yui; Kim, Suk; Ichikawa, Yasuaki; Endo, Yasuyuki; Watanabe, Kenta; Shimizu, Takashi; Watarai, Masahisa
Abstract : Brucella canis, a facultative intracellular pathogen, is the causative agent of canine brucellosis. The diagnosis of canine brucellosis is based on bacteriological examination and serological methods, including agglutination and gel diffusion tests. In this study, four recombinant antigens, heat shock protein 60, rhizopine-binding protein, Cu-Zn superoxide dismutase, and hypothetical protein (Ag 4), were constructed. These antigens were coated on latex beads and their usefulness in the serological diagnosis of canine brucellosis was examined. All recombinant antigens showed specific reaction with sera from B. canis -infected dogs in Western blotting. In a microplate agglutination test, mixing sera from B. canis -infected dogs, but not sera from B. canis -free dogs, with single or multiple antigens-coated latex beads produced clear agglutination. Moreover, the antigen-coated latex beads did not show nonspecific agglutination in hemolyzed serum samples. A survey of canine serum samples conducted by the microplate agglutination test using single antigen-coated latex beads showed that this method would be useful in the serological diagnosis of canine brucellosis. Further investigations using more serum samples are required to confirm the usefulness of our method.